A grounded theory of educational psychologists' mental health casework in schools: connection, direction and reconstruction through consultation. Issue 4 (1st October 2020) - Zafeiriou, Maria Evrydiki; Gulliford, Anthea
ABSTRACT: Educational psychologists (EPs) in England are identified as key to specialist mental health provision in schools yet are underrepresented in policy development. This study examined EPs' mental health casework in schools as one aspect of the professional contribution in this area. Data gathered from interviews with EPs were analysed though constructivist grounded theory (GT) methods. The resulting GT drew from psychotherapeutic attachment theories, person-centred counselling, self-determination theory, solution-focused thinking, and from ecological and consultation theories. EPs used two distinct but interacting processes in mental health casework. One involved facilitating a secure base offering emotional containment for overwhelmed adults (staff, parents). The other engaged adults in cognitively demanding problem-solving activities, challenging perceptions, leading to cognitive and behavioural change, and in turn to systemic adaptations. Limitations and implications are discussed.